The translation of Satan’s Slave 2 Communion: An analysis of pronoun usage in movie translation from Indonesian to English - Swetika, Amanda Widhi; Prihantoro, Prihantoro (Universitas Islam Sultan Agung, 2024)
In this research, we analyzed the frequency, usage, and changes of pronouns in the translation of Satan’s Slave 2: Communion. This research was conducted by examining changes in subject or object pronouns from Indonesian to English in the movie subtitle. We transferred the clean version of the subtitle into a spreadsheet, into which we incorporated necessary context information such as presented in 3 categories; pronoun to pronoun, pronoun to omission, and pronoun to reference. The results show that the use and change of pronouns in the translation process of Satan’s Slave 2 are attached by at least two aspects: grammatical and socio-cultural aspects. The difference in the principle of linguistic rules between Indonesian and English becomes an important factor behind the transposition and modulation of pronouns in the translation process. The sociocultural differences between Indonesian and English also need to be carefully examined before translating, because there are significant differences in the use of pronouns between Indonesian and English, especially related to sociocultural aspects that affect the use of language towards interlocutors.